Pengaruh Kinerja Keuangan Terhadap Harga Saham pada Perusahaan Perbankan di JII - Kusuma Ningrum, Cahya; Prastya, Galih; Putri Zahro, Alfani; Ti'anatud Diniati, Bintis (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of financial performance as measured by the financial ratios CR, LDR, ROA, ROE, BOPO and NIM on stock prices. The population of this study are banking companies listed on the Jakarta Islamic Index (JII) for the period 2021-2023. The sampling technique was purposive sampling method. This type of research is descriptive quantitative through the data analysis method of classical assumption test, panel data regression analysis, and hypothesis testing. The findings of this study indicate that ROE and ROA have a significant positive effect on stock prices, CR and BOPO have an insignificant negative effect on stock prices, and CR and NIM have an insignificant positive effect. Simultaneously, CR, LDR, ROE, ROA, BOPO, and NIM variables have a significant effect on stock prices.